2018
DOI: 10.1111/nhs.12573
|View full text |Cite
|
Sign up to set email alerts
|

Differing pathways to resiliency: A grounded theory study of enactment of resilience among acute care nurses

Abstract: It is well‐recognized that nurses are exposed to high levels of stress, thus resilience has been postulated as a key trait in enabling nurses to cope successfully and remain in the profession. In this qualitative study, we used Glaser's approach to grounded theory. Nine nurses who scored low and nine nurses who scored high on the Connor–Davidson Resilience Scale were recruited for one‐on‐one semistructured interviews of the factors contributing to their work‐related stress and how they overcome these stressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
0
21
2
Order By: Relevance
“…Considering the inherent stress of the working environments of HCWs’, especially during the COVID‐19 period, resilience can be seen as a key attribute of HCWs. Previous studies found that highly‐resilient nurses reported better outcomes, such as lower burnout, depression and anxiety rates (Manzano García & Ayala Calvo, 2012 ), higher levels of job satisfaction (Matos et al, 2010 ) and the adoption of more active coping approaches (Ang et al, 2019 ; Wu et al, 2013 ). Resilience has also been shown to be positively associated with life satisfaction, self‐esteem, positive affect and health‐promoting behaviours (Cohn et al, 2009 ; Huang et al, 2018 ; Ma et al, 2013 ), while low levels of resilience have been associated with negative affect (Alarcón et al, 2020 ) in other populations.…”
Section: Backgroundsmentioning
confidence: 99%
“…Considering the inherent stress of the working environments of HCWs’, especially during the COVID‐19 period, resilience can be seen as a key attribute of HCWs. Previous studies found that highly‐resilient nurses reported better outcomes, such as lower burnout, depression and anxiety rates (Manzano García & Ayala Calvo, 2012 ), higher levels of job satisfaction (Matos et al, 2010 ) and the adoption of more active coping approaches (Ang et al, 2019 ; Wu et al, 2013 ). Resilience has also been shown to be positively associated with life satisfaction, self‐esteem, positive affect and health‐promoting behaviours (Cohn et al, 2009 ; Huang et al, 2018 ; Ma et al, 2013 ), while low levels of resilience have been associated with negative affect (Alarcón et al, 2020 ) in other populations.…”
Section: Backgroundsmentioning
confidence: 99%
“…The concept of resilience refers to the ability to adapt to adversity (McAllister et al, 2015). Individuals with high levels of resilience tend to perceive life challenges from a positive perspective (Ang, Uthaman, Ayre, Lim, & Lopez, 2019;Li, Eschenauer, & Persaud, 2018). Resilience plays an important role in inducing mental health and behavior and improving quality of life to cope with anxiety and depression from lifethreatening chronic diseases (Cho & Lee, 2019).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The financial implications of this loss of nurses have been estimated at $137 billion (Volmer, 2020 ) even while health care organizations invest in multiple resources to retain nurses. Professional commitment and resilience have been identified as key factors contributing to retention (Alharbi et al, 2019 ; Ang et al, 2019 ; Argus & Sekvaraj, 2020 ). If commitment and resilience are related to nurses' intent to leave the nursing profession, then strategies for strengthening commitment and resilience are vital aims that may help support incoming and existing nurses (Argus & Sekvaraj, 2020 ; Lee et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%